Temporal Dynamics of the Integration of Intention and Outcome in Harmful and Helpful Moral Judgment - Gan, Tian; Lu, Xiaping; Li, Wanqing; Gui, Danyang; Tang, Honghong; Mai, Xiaoqin; Liu, Chao; Luo, Yue-Jia (Frontiers in Psychology, 2016)
The ability to integrate the moral intention information with the outcome of an action plays a crucial role in mature moral judgment. Functional magnetic resonance imaging (fMRI) studies implicated that both prefrontal and temporo-parietal cortices are involved in moral intention and outcome processing. Here, we used the event-related potentials (ERPs) technique to investigate the temporal dynamics of the processing of the integration between intention and outcome information in harmful and helpful moral judgment. In two experiments, participants were asked to make moral judgments for agents who produced either negative/neutral outcomes with harmful/neutral intentions (harmful judgment) or positive/neutral outcomes with helpful/neutral intentions (helpful judgment). Significant ERP differences between attempted and successful actions over prefrontal and bilateral temporo-parietal regions were found in both harmful and helpful moral judgment, which suggest a possible time course of the integration processing in the brain, starting from the right temporo-parietal area (N180) to the left temporo-parietal area (N250), then the prefrontal area (FSW) and the right temporo-parietal area (TP450 and TPSW) again. These results highlighted the fast moral intuition reaction and the late integration processing over the right temporo-parietal area.